SAMPERS – Erfarenheter av komplexa modeller i ett komplext utvecklingsprojekt - Algers, Steffan; Beser, Muriel; Sveder, Gunnar Johansson (Proceedings from the Annual Transport Conference at Aalborg University, 2000)
Swedish transportation authorities have a long tradition of developing traffic demand models. The first generation of national models was developed in the beginning of the 1980s, a second generation during the first half of 1990s. These models have also been frequently used in a large number of projects but also as a part of the regular national strategic transport investment plan. The national planning process has been a four-year cycle of revising a ten- year investment scheme. The first step in this process is to undertake an analysis to decide on a general policy (like promoting accessibility or focus on environmental protection). Here the models are used to analyse a few main alternatives, representing major differences in transportation policy and economic development (such as heavily increased petrol taxes to reduce carbondioxide emission).